Management of Facilities and Infrastructure at MTS Negeri 2 Palembang: Pengelolaan Sarana Dan Prasarana Di MTS Negeri 2 Palembang - Sari, Novita Eka; Saputra, Ade Akhmad (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This study focuses on the policy of managing educational facilities and infrastructure at MTs Negeri 2 Palembang, which represents one of the key aspects in supporting the effectiveness of the learning process and the achievement of educational goals. The main objective of this research is to describe and analyze how the management policy is designed, implemented, and evaluated, as well as to identify the supporting and inhibiting factors in its implementation. This research employs a descriptive qualitative approach with data collection techniques that include in-depth interviews, direct observation, and document analysis. The data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the policy for managing facilities and infrastructure at MTs Negeri 2 Palembang has followed a structured process, ranging from planning, procurement, utilization, to maintenance. However, its implementation has not been fully optimal due to challenges such as budget limitations, suboptimal coordination between work units, and minimal stakeholder participation in the evaluation process. The implications of this study highlight the importance of strengthening the internal evaluation system and fostering broader collaboration between the madrasah, relevant institutions, and the community to establish sustainable and participatory educational facility management.